The down-regulation of SLC7A11 enhances ROS induced P-gp over-expression and drug resistance in MCF-7 breast cancer cells - Chun Ge (Nature Portfolio, 2017)
Abstract Adriamycin (ADR) induces the over-expression of P-glycoprotein (P-gp) and multiple drug resistance in breast cancer cells. However, the biochemical process and underlying mechanisms are not clear. Our previous study revealed that ADR increased reactive oxygen species (ROS) generation and decreased glutathione (GSH) biosynthesis, while N-acetylcysteine, the ROS scavenger, reversed the over-expression of P-gp. The present study showed that ADR inhibited the influx of cystine (the source material of GSH) and the activity of the SLC7A11 transporter (in charge of cystine uptake) in MCF-7 cells. For the first time, we showed that the down-regulation/silence of SLC7A11, or cystine deprivation, or enhanced ROS exposure significantly increased P-gp expression in MCF-7 cells. The down-regulation of SLC7A11 markedly enhanced ROS induced P-gp over-expression and drug resistance in MCF-7 cells; a combination of either an inhibited/silenced SLC7A11 or cystine deprivation and increased ROS dramatically promoted P-gp expression, which could be reversed by N-acetylcysteine. In contrast, the over-expression of SLC7A11, or supplementation with sufficiently cystine, or treatment with N-acetylcysteine significantly decreased P-gp expression and activity. It was suggested that ROS and SLC7A11/cystine were the two relevant factors responsible for the expression and function of P-gp, and that SLC7A11 might be a potential target modulating ADR resistance.